Barriers Limiting the Use of Google Classroom for Learning Vocational and Entrepreneurship Courses - Adigun Boluwatife Joshua; Obielodan Omotayo Olabo; Onojah Amos Ochayi; Aderoju Adekola Musiliu; Onojah Adenike Aderogba (ASEAN Journal of Science and Engineering Education, 2022)
The dream of every undergraduate is to get a fascinated well-paid Job after school. One of the courses that could aid students’ employment is the vocational and entrepreneurship courses. Due to the high number of students who partake in this course, some technologies were employed for the instructional process. One of such is the Google classroom. However, there are some complains from students on these learning technological platforms. This study therefore investigates the barriers limiting the use of google classroom for learning vocational and entrepreneurship courses. This study employs the survey method, and 250 undergraduates were purposively sampled. The findings established that Poor power supply, loss of class control, High cost of purchasing relevant materials, Lack of adequate support system and laziness encouragement are barriers that hinder students’ use of google classroom for learning vocational and entrepreneurship courses. The study concluded that some barriers which hinders students from using Google classroom for learning should be resolved. It was however recommended that the use of google classroom should be encouraged in schools, not only for learning vocational and entrepreneurship courses but for other courses.